Post-Prostatectomy Incontinence : Evaluation and Management - Singla, Ajay; Comiter, Craig (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive, state - of - the art review of this new and emerging field, as the number of men who suffer from post-prostatectomy incontinence increases by greater than 10,000 per year. How to evaluate and manage this devastating disorder has become a necessary part of nearly every urologic practice. This book serves a valuable resource for physicians with an interest in managing patients with post-prostatectomy incontinence. In addition, treatment includes algorithms and suggested office evaluation that will help guide conservative management that is appropriate for most patients. The text provides insight into the history of male incontinence surgery, as well as the current surgical techniques for the operative management of post-prostatectomy incontinence in those who fail conservative management. This text reviews current data regarding surgical outcomes for the most common and newly developed incontinence procedures, as well as step-by-step descriptions of the key surgical steps necessary for success. All chapters are written by world renowned experts in this field and include the most up to date clinical information.
Keywords: Medicine.; Rehabilitation medicine.; Urology.; elektronické knihy; electronic books